(untitled) (Raparin Journal of Humanities (RJH), 2023)
Hotel training is crucial to equipping staff with the knowledge and abilities they need to advance their performance and boost the standard of specialized hotel services، which will have positive effects on the professional، financial، and social spheres. The purpose of the study is to identify the training policies، programs، and standards used in Sulaymaniyah’s four- and five-star hotels as well as the standards used to assess employee performance. It also seeks to pinpoint the major issues and roadblocks that prevent the four- and five-star hotels from implementing efficient training programs. The research covered both theoretical and practical issues، and the descriptive analytical approach was employed. On the theoretical side، a number of books، theses، and Arabic publications that focused on hotel training were used as references. The measurement tool (the questionnaire) was created and provided to a random sample of guests in those hotels on the field side. The validity of the hypotheses was examined using the SPSS statistical processing application and a five-point Likert scale. The research produced a number of recommendations and conclusions، the most significant of which is that there is uncertainty in the activation and implementation of hotel training policies in the public and private sectors، and that programs tend to be generally focused on generalization rather than specialization and diagnosis، as well as the absence of hotel professional centers in the public and private sectors. Moreover، there aren’t any facilities for professional training dedicated to the growth and development of hotel staff. The necessity to pay attention to the function of hotel training in boosting the performance level of employees in Sulaymaniyah hotels as one of the dimensions to improving the performance of hotel services in Sulaymaniyah is one of the most crucial recommendations. The more readily available these programs are، the higher the level of performance of employees in Sulaymaniyah’s hotels. This is in addition to working on the supply of appropriate training programs to increase the performance of the staff level of hotel services.